China's Encounters with the West: The Case of Chinese Multinationals (MNCS) in Africa - Kopiński, Dominik (Kontakty Chin z Zachodem: przypadek chińskich korporacji międzynarodowych w Afryce, 2010)
This paper explores the recent phenomenon of Chinese multinationals (MNCs) who have made significant inroads into Africa claiming their share in the continent's riches and markets. They pose a major challenge to the Western world whose dominance in the region has been undisputed for many years. Most of the Chinese MNCs are state-owned companies whose expansion overseas has been greatly facilitated and encouraged by the Chinese government. The main driving force of Chinese MNCs is to secure access to energy resources and raw materials needed to feed the burgeoning economic growth in China. There are several features that make the Chinese MNCs distinctive vis-à-vis European, American or Japanese counterparts.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 387-398
Keywords: multinationals; FDI; state-owned companies; Sino-African relations